Estágio Curricular e Formação do Habitus Docente em Educação Musical - Benvenuto, João Emanoel Ancelmo (2012)
This study was developed at the Education Course Post-graduation Program from Federal Ceará University (UFC), in Education, Curriculum and Teaching research line applied in Music Teaching. This research aims to study the teaching habitus education process during the insertion period of the UFC student from the Music Teaching Program, in the city of Fortaleza. The research purpose is to investigate what the elements which collaborate on the construction of this habitus together with teaching practicum are. By investigating the curriculum moment of music teaching practicum, I seek to research what the individuals involved who have active participation on the construction and creation of the pedagogical meaning are. The reflections presented here show supervised practicum gives to students, as an opportunity, the possibility of practical teaching comprehension carried out by the music teacher and the development of more secure teaching abilities by them. It is necessary to highlight the importance of teaching trainment for education of the musical teacher, for it is in the teaching practice the teacher will find investigation topics and reflections to evaluate his teaching technique. As to the value attributed to Music Education and on the recent music teaching situation view, the research has the purpose of investigating the trainee students’ education process related to hi performance in the classes, in order to comprehend how this appropriation by the music teacher happens.